Influence factors in increasing brand loyalty through customer engagement on MPV cars - Indawati Lestari; Desy Astrid Anindya; Finta Aramita (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Customer engagement can be formed with supportive social media marketing and brand experience. But in this case, the company has not fully created the experience and social media consumers need. The company’s strategy to increase car sales certainly needs to be promoted. This study aims to determine and analyze the influence of social media marketing and brand experience on brand loyalty through customer engagement on MPV product users in Medan City. The population in this study amounted to 62,296 people. Sampling using purposive sampling with sample criteria, namely consumers who use cars with the Toyota brand and have used more than 3 (three) years. The sample calculation used the slovin formula with a total of 397 respondents. The research data used primary data and secondary data. The data analysis carried out is path analysis. The results of sub 1 analysis show that social media marketing and brand experience positively and significantly affect customer engagement. The results of sub 2 analysis show that social media marketing and brand experience positively and significantly affect brand loyalty through customer engagement. When social media marketing and brand experience increase, customer engagement will also increase, so that brand loyalty increases.